A coherent method for combined stable magnesium and radiogenic strontium isotope analyses in carbonates (with application to geological reference materials SARM 40, SARM 43, SRM 88A, SRM 1B) - Jessica A. Stammeier; Oliver Nebel; Dorothee Hippler; Martin Dietzel (MethodsX, 2020)
We undertook 87Sr/86Sr analyses for a range of carbonate bearing geological reference materials, and combined these with δ26Mg for a subset of samples. Following chemical purification in a series of chromatographic extractions, isotope ratios were measured by Multi-Collector-ICP-MS using a Plasma II (Nu instruments, Wrexham, UK). To validate efficient sample digestion procedures of carbonate fractions, total samples were treated with either 3 mol l−1 HNO3 and 0.5 mol l−1 HCl, respectively. Results of both leaching procedures are identical within reproducibility. Reference values for SRM 88A (formerly NBS 88A), SRM 1B (formerly NBS 1B), SARM 40, SARM 43, JDo-1, JLs-1, and San Carlos olivine range from 0.70292 to 0.73724 in 87Sr/86Sr and from -2.80 to -0.41 ‰ for δ26Mg, respectively. This set of geological reference materials can be used for sedimentary rock material with different carbonate mineral and matrix composition as quality control measurements of combined stable Mg and radiogenic Sr isotope analyses. • We present a protocol that facilitates the chemical separation of Mg and Sr in carbonate bearing geological reference materials including 87Sr/86Sr and δ26Mg of certified reference materials.